Acute myocardial infarction, intraventricular thrombus and risk of systemic embolism - Hudec, Stepan; Hutyra, Martin; Precek, Jan; Latal, Jan; Nykl, Radomir; Spacek, Miloslav; Sluka, Martin; Sanak, Daniel; Tudos, Zbynek; Navratil, Karel; Pavlu, Ludek; Taborsky, Milos (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
The development of left ventricular thrombus (LVT) is a well-known and serious complication of acute myocardial infarction (AMI) due to the risk of systemic arterial embolism (SE), which is variable in its clinical picture and has potentially serious consequences depending on the extent of target organ damage. SE results in an increase in mortality and morbidity in these patients. LVT is one of the main causes of the development of ischaemic cardio-embolic cardiovascular events (CVE) after MI and the determination of the source of cardiac embolus is crucial for the initiation of adequate anticoagulant therapy in secondary prevention. Echocardiography holds an irreplaceable place in the diagnosis of LVT, contrast enhancement provides higher sensitivity. The gold standard for LVT diagnosis is cardiac magnetic resonance imaging, but it is not suitable as a basic screening test. In patients with already diagnosed LVT, it is necessary to adjust antithrombotic therapy by starting warfarin anticoagulation for at least 6 months with the need for echocardiographic follow-up to detect thrombotic residues. The effect of prophylactic administration of warfarin in high-risk patients after anterior AMI does not outweigh the risk of severe bleeding complications and does not result in a decrease in mortality and morbidity. At the present time, there is not enough evidence to use direct oral anticoagulants in this indication.
Keywords: Coronary Thrombosis; systemic arterial embolism; Percutaneous Coronary Intervention; therapy; stroke; lidé; koronární angioplastika; Myocardial Infarction; ST segment elevation myocardial infarction; embolie; Embolism; srdeční komory; Humans; koronární trombóza; Heart Ventricles; infarkt myokardu; left ventricular thrombus